Dynamic capabilities and competitive advantages as mediator variables between market orientation and business performance - Correia, R. J.; Dias, J. G.; Teixeira, M. S. (Journal of Strategy and Management, 2020)
Purpose: This paper aims to explore a new causal link between market orientation and business performance by introducing dynamic capabilities as a mediator of the relationship between market orientation and competitive advantages, which ultimately determine business performance. Design/methodology/approach: The mediating roles of dynamic capabilities and competitive advantages are tested with a sample of 1,190 Portuguese firms using a structural equation model. Findings: The results confirm the hypotheses regarding the mediating roles of the competitive advantages (differentiation and cost leadership) in the relationship between dynamic capabilities and business performance. Additionally, dynamic capabilities also mediate the relationship between market orientation and competitive advantages. Practical implications: This study shows that business performance depends on the capacity of firms to collect the best market information on customers and competitors, to disseminate this information throughout their internal structure and ultimately optimize its use to respond appropriately to market challenges and trends. These will provide firms with a set of capabilities and a competitive advantage. Originality/value: This study provides empirical evidence on the understanding of the relationship between market orientation and performance, through the mediating effects of both dynamic capabilities and competitive advantages.